Uji Resistensi Nyamuk Aedes Aegypti terhadap Sipermetrin 0,05% di Pelabuhan Sungai Duku dan Bandara Sultan Syarif Kasim II Pekanbaru - Dedes Handayani; Zuhirman Zuhirman; Ridwan Manda Putra (SEHATI: Jurnal Kesehatan, 2021)
Control of use of chemical insecticides is one way to reduce the vector borne disease dengue hemmorrhagic fever (DHF)which are caused by the mosquito Aedes aegypti. This study aims to determine the susceptibility status of Aedes aegypti to cypermethrin insecticide, the differences susceptibility status in the Duku River Port and Sultan Syarif Kasim Airport Pekanbaru.This study was an descriptif study with cross-sectional design. Egg and Larva Aedes aegypti mosquito sample collected from ovitrap and larva-place from Duku River Port area and Sultan Syarif Kasim II Airport. Test of susceptibility to cypermethrin 0.05 % was done using impregnated paper refers to the WHO method, T independent test to considaret susceptibility status different both area.The result showed that Ae. aegypti in Duku River Port area and Sultan Syarif Kasim II airport areas have been toleran cypermethrin 0.05%.There is no difference in the susceptibility of cypermethrin 0,05% to the population of Aedes aegypti in Duku River Port and Sultan Syarif Kasim II Airport.